1985
DOI: 10.1083/jcb.101.4.1288
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the glyoxysome-peroxisome transition in germinating cucumber cotyledons using double-label immunoelectron microscopy.

Abstract: Microbodies in the cotyledons of cucumber seedlings perform two successive metabolic functions during early postgerminative development. During the first 4 or 5 d, glyoxylate cycle enzymes accumulate in microbodies called glyoxysomes. Beginning at about day 3, light-induced activities of enzymes involved in photorespiratory glycolate metabolism accumulate rapidly in microbodies. As the cotyledonary microbodies undergo a functional transition from glyoxysomal to peroxisomal metabolism, both sets of enzymes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 23 publications
2
79
0
2
Order By: Relevance
“…The transition of seedling peroxisomes to leaf peroxisomes appears to be a gradual process, as several reports described a transitional form of peroxisomes containing both glyoxylate cycle and photorespiratory enzymes (Titus and Becker, 1985;Nishimura et al, 1986;Sautter, 1986). We do not know which of these three types of peroxisomes is subjected to autophagy ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition of seedling peroxisomes to leaf peroxisomes appears to be a gradual process, as several reports described a transitional form of peroxisomes containing both glyoxylate cycle and photorespiratory enzymes (Titus and Becker, 1985;Nishimura et al, 1986;Sautter, 1986). We do not know which of these three types of peroxisomes is subjected to autophagy ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…As a control, we compared the expression pattern of ATG in cotyledons (see Supplemental Figure 5 online). We focused on genes encoding the ATG8 conjugation system because the expression of these genes is often regulated developmentally (van der Graaff et al, 2006;Chung et al, 2009). A preliminary search in the Genevestigator database (http://www.genevestigator.com) revealed that ATG3, ATG8b, ATG8g, and ATG8i showed higher expression levels in hypocotyls than in cotyledons.…”
Section: Expression Of Atg7 Is Induced In Hypocotyls But Not In Cotylmentioning
confidence: 99%
“…Immunolabeling experiments in greening cucurbit cotyledons directly demonstrate the presence of both photorespiration enzymes and glyoxylate cycle enzymes in the same peroxisomes (Titus and Becker, 1985;Nishimura et al, 1986;Sautter, 1986). Moreover, MLS is stable following in vitro import into early pumpkin (Cucurbita sp Amakuri Nankin) seedling peroxisomes but degraded after import into transitional peroxisomes (Mori and Nishimura, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…During seedling development, peroxisome functions shift from fatty acid utilization to photorespiration (Titus and Becker, 1985;Nishimura et al, 1986;Sautter, 1986;. Autophagy mutants accumulate peroxisomal proteins (Shibata et al, 2013;Yoshimoto et al, 2014) and peroxisomes Yoshimoto et al, 2014) during this transition, suggesting a role for pexophagy in clearing obsolete peroxisomes.…”
Section: Quality Control and Pexophagymentioning
confidence: 99%
“…In addition to the core processes of b-oxidation and ROS detoxification, plant peroxisomes house diverse specialized functions (for review, see Reumann and Bartel, 2016) that may change during development (Titus and Becker, 1985;Nishimura et al, 1986;Sautter, 1986; or in response to environmental cues (for review, see Goto-Yamada et al, 2015). For example, plant peroxisomes sequester enzymes acting in photorespiration, which is important when ribulose-1,5-bisphosphate carboxylase/oxygenase fixes O 2 instead of CO 2 .…”
Section: Photorespiration: Not Just For Chloroplastsmentioning
confidence: 99%